2019
DOI: 10.1002/mame.201800789
|View full text |Cite
|
Sign up to set email alerts
|

Thermal‐Insulation, Electrical, and Mechanical Properties of Highly‐Expanded PMMA/MWCNT Nanocomposite Foams Fabricated by Supercritical CO2 Foaming

Abstract: Poly(methyl methacrylate) (PMMA) foams exhibit many advantages over the most popular polystyrene (PS) foams, which make them an ideal candidate for thermal insulation application. First, PMMA has lower carbon content, lower burning rate, smaller heat release rate, and lower smoke emission than PS. [7] So, PMMA foams need less flame retardants than PS foams when used as construction thermal insulation materials, which helps reduce the overall production costs and mitigate the greenhouse effect. Second, PMMA can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Our study should help enhancing and optimizing conditions of nano foaming. Foams, when reducing both cell size and density at the same time, are intended to exhibit enhancement of several properties, such as high thermal insulation [25] or high performance mechanical properties [26] (damping) or else useful for filtration [13].…”
Section: Introductionmentioning
confidence: 99%
“…Our study should help enhancing and optimizing conditions of nano foaming. Foams, when reducing both cell size and density at the same time, are intended to exhibit enhancement of several properties, such as high thermal insulation [25] or high performance mechanical properties [26] (damping) or else useful for filtration [13].…”
Section: Introductionmentioning
confidence: 99%
“…The supercritical fluid foaming process can greatly reduce the density of the composites and fabricate a porous structure in the polymer matrix. Therefore, this technique is highly attractive as it possesses a number of benefits such as energy saving [17,18], environmental protection [19,20], thermal insulation [21,22], and vibration and noise reduction [23]. A large number of studies have reported that the introduction of the microcellular structure is conducive in improving the EMI shielding properties of conductive polymer composites [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Polymer foams with unprecedented thermal-insulation properties play a vital role to improve energy efficiency through achieving high-efficiency thermal insulation. [61] Meanwhile, the foams with closed cell structure also provide the certain structural rigidity to the foams comparing with the foams with opened cell structure. [62] In addition, the unsurpassed and most easily available substances for the purpose of the low thermal conductivity are various kinds of gases.…”
Section: Thermal Conductivementioning
confidence: 99%